PENGARUH PENDIDIKAN KESEHATAN TENTANG GIZI TERHADAP TINGKAT PENGETAHUAN GIZI PADA ANAK USIA SEKOLAH - Honest, Irianto; M, Tri; G, Elpinaria; R, Yosy; Gita, Irma; Sasue, Marisa; T, Sasni; J, Rahma; Laia, Julianto; D, Rani (Poltekkes Kemenkes Pontianak, 2025)
Background: Balanced nutrition is a daily food arrangement that contains various nutrients of the type and amount that are in accordance with the needs of the body. Elementary school children (SD) are children aged 6-12 years, Growth and development of children really need adequate nutrition so that there are no deviations in the growth and development of children, Factors that can affect a person's nutrition are diet. Diet is closely related to the type, amount and composition of food consumed every day. Fulfillment of good food for children will affect the nutritional status of children. Purpose: To determine the effect of nutrition health education on the level of nutritional knowledge of school children. Methods: Pre-experimental with “one group pre-test and post-test design”. Sample selection using total sampling technique with a total sample size of 30 respondents. The instrument used was a questionnaire and the data analysis test used the Wilcoxon test. Results: Based on the results of this study, the p value of 0.000 ≤ 0.05 means that Ha is accepted and Ho is rejected. Conclusion: The level of knowledge is influenced by health education that can increase or improve knowledge and understanding of nutrition, especially in children.